Design and development of an electromygraphy (EMG) based active elbow orthosis with feedback control / Mubeenah Titilona Sanni - Mubeenah Titilona , Sanni (2017)
The project presents the design and development of an electromyography based active elbow orthosis for self-rehabilitation of post stroke patients or patients with elbow injuries. The elbow could lose its functionality as a result of multiple reasons however Humans depend on their elbow and the hand as a whole to carry out various activities of everyday life. Rehabilitation by physiotherapist is the traditional method to regain elbow functionality but it requires the patient to travel frequently to the hospital and the extra cost of consulting a physiotherapist. This gave rise to the need for developing an elbow orthosis which can be used for self-therapy, eliminating the cost and stress of visiting a physiotherapist. The active orthosis measures the patient’s activity using Electromyography and the electrical signal obtained from this sensor is used to control the actuator that drives the orthosis. The orthosis is battery-powered with an active range of 60 – 140 degrees. The actuator for the orthosis generates a torque of 2.9Nm and the frame is made of light-weight thermoplastic polypropylene. The device was tested on five different subjects to determine the performance of the device in helping to flex and extend the patient’s elbows. The range of movement of the joint when the subject was not wearing the orthosis and when the subject was wearing the orthosis was recorded using Kinovea software and the joint angle movement was thus calculated and compared. The analysis of the elbow orthosis using Kinovea software showed that the device is capable of helping in the flexion and extension of the human elbow through the normal ROM. Keywords: Active elbow orthosis, Self-Rehabilitation, Electromyography